Study of Adsorption Characteristics a Low-Cost Sawdust for the Removal of Direct Blue 85 Dye from Aqueous Solutions - Rahmah Hashim Abdullah; Amjed Mirza Oda; Alaa Rasheed Omran; Ameer Salem Mottaleb; Teeba Mudhefer Mubarakah (Indonesian Journal of Chemistry, 2018)
The performance sawdust as a low cost adsorbent to remove Direct Blue 85 (DB85) dye from aqueous solutions has been evaluated. The characteristic of sawdust analyzed by FTIR and XRD. The removal percentage of this dye was studied at different experimental conditions such as contact time, adsorbent dosage, particle size, temperature, and pH. The optimum removal percentage value was found at pH 2.Temperature also has a positive impact on adsorption, where the adsorption of this dye on the sawdust increased as the temperature increased. High values of correlation coefficient signified that the adsorption of (DB85) dye on the surface of sawdust obey Langmuir and Freundlich adsorption isotherms.